2002
DOI: 10.2135/cropsci2002.1615
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Competitive Success of an Intraseeded Creeping Bentgrass Cultivar into an Established Putting Green

Abstract: several months during establishment. The financial loss due to the lack of play is significant to the golf club. Intraseeding is a popular approach for converting established golfIntraseeding is an alternative approach to establishcourse putting greens to a more desirable cultivar of the same species ment of a new turfgrass stand. The concept of intraseedwithout killing the existing turf. This study was conducted to determine the competitive success of an intraseeded creeping bentgrass (Agrostis ing is to slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Efforts to convert ‘Penncross’ creeping bentgrass ( Agrostis palustris Huds.) putting greens to the cultivar G‐2 were futile unless glyphosate was employed (Kendrick and Danneberger, 2002). Establishing Kentucky bluegrass ( Poa pratensis L.) seedlings in a mature stand of perennial ryegrass was unsuccessful unless a high seeding rate (196 kg ha −1 ) was employed in combination with suppressing the perennial ryegrass by scalping the first few weeks after seeding (Kraft et al, 2004).…”
mentioning
confidence: 99%
“…Efforts to convert ‘Penncross’ creeping bentgrass ( Agrostis palustris Huds.) putting greens to the cultivar G‐2 were futile unless glyphosate was employed (Kendrick and Danneberger, 2002). Establishing Kentucky bluegrass ( Poa pratensis L.) seedlings in a mature stand of perennial ryegrass was unsuccessful unless a high seeding rate (196 kg ha −1 ) was employed in combination with suppressing the perennial ryegrass by scalping the first few weeks after seeding (Kraft et al, 2004).…”
mentioning
confidence: 99%
“…Converting from Kentucky bluegrass to no-mow, low-input grass requires conversion methods that allow for adequate turfgrass establishment and provide long-term success. Methods for turfgrass conversion that have been used in the golf course industry include the use of non-selective herbicides and fumigants, tillage or sod removal, and interseeding (13,14,15,18).…”
mentioning
confidence: 99%
“…Attempts at shifting the population of putting greens and other turf areas via interseeding have been tried in the past and there is clear disagreement between academia and industry concerning the success of this conversion technique. A number of individuals within academia contend the process is without merit Cattani and Nowak, 2001; Kendrick and Danneberger, 2005;Rossi, 1999;Kendrick and Danneberger, 2002;). Yet, many researchers from industry and turfgrass practitioners claim to find value in the practice (Brilman, 2009;Miller, 2004;Ross, 2006;Brede, 2006;Brede, 2007).…”
Section: Traditional Renovation and Succession Of Plant Communitiesmentioning
confidence: 99%
“…were able to convert 35% of a perennial ryegrass sward to creeping bentgrass over a three year period, while seeding into a polystand of annual bluegrass, perennial ryegrass, and Kentucky bluegrass resulted in no more than 3% creeping bentgrass. Kendrick and Danneberger (2002) and Dant et al (2005) indicated that the effectiveness of the intraseeding techniques was quite limited unless competition from the existing turf was removed. Cattani and Nowak (2001) found that establishment of L-93 in an existing sward of Penncross was only successful when the overall condition of the existing turf was compromised to the extent that it would be unplayable.…”
Section: Traditional Renovation and Succession Of Plant Communitiesmentioning
confidence: 99%
See 1 more Smart Citation